Menjelajahi Dukungan Sosial Bagi Mualaf Baru di Kota Makassar: Perspektif Kontemporer - Awaru, A. Octamaya Tenri; Hidayat, Andi Rahmat; Syukur, Muhammad; Rahman, Abdul (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2023)
Social support helps adapt and strengthen the Islamic identity of converts in a diverse society. Social support will boost self-esteem, reduce stress, give a sense of belonging and help clarify self-esteem. The purpose of this study is to find out how the form of social support for converts and the benefits of social support felt by converts in Makassar City. This research is descriptive qualitative research with a phenomenological approach. The informant in the study was a convert who was domiciled in Makassar City which was determined using snowball sampling techniques. Data collected by observation and interviews are interpreted and interpreted according to information from informants. The data found are checked for validity using checking techniques and increasing the persistence of observations. Data analysis techniques go through 3 stages, namely data reduction, data presentation, conclusion drawing or verification. The results of the study found that the form of social support provided by the people of Makassar City to Mulaf was emotional support; support in the form of awards; instrumental support, and support in the form of information. The benefits of social support felt by converts are to eliminate doubts / anxieties; increase self-confidence; help to understand new religions; increase religious commitment. The people of Makassar City need to expand their understanding of Islam and provide positive and inclusive social support to converts to help them adapt and strengthen their Islamic identity.